Comparative analysis of urban condition the residential market area with the use of GIS tools - Renigier-Biłozor, Małgorzata; Biłozor, Andrzej (International Conference “Environmental Engineering”, 2017)
Analysis of the significance of structural and spatial similarities aims to identify homogeneous categories of real estate markets on the basis of the urban features of the area. Real estate markets play an increasingly important role in the global economy and investment, which is why the reliable view of residential market area became an essential tool in the process of investment planning. The positions of particular cities that will be developed by themselves according to established criteria can be crucial when choosing an investment location, and can affect the range of influence of the central site for the entire region. The aim of the research is to conduct the comparative analysis of the condition of residential market area in relation to their urban features. The social, spatial, economic and residential factors will be analysed taking into consideration their exogenous structure. The assessments of coherence and diversification of esidential markets similarities in terms of their mutual location will be shown in the article. The developed methodology will be presented on the example of the largest residential markets centers in Poland. Due to the dynamic and complex nature of the information related to real estate (in various residential regions), and increase the objectivity of the results, the assumptions of data mining analysis and GiS tools will be used.